VALIDITAS PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERORIENTASI PROBLEM BASED LEARNING PADA MATA PELAJARAN IPAS KELAS V SD NEGERI 17 PONTIANAK KOTA - Marco, Marco (Universitas Tanjungpura, 2025)
This study generally aims to describe the validity of Problem-based learning worksheets in class IV IPAS learning at SDN 17 Pontianak City. This research is a type of development research (Research & Development) with reference to the ADDIE development model. The research method used is a mixed method between quantitative research and qualitative research. The data source of this research is the validation results from 2 material experts, 2 language experts, and 2 design experts. The data collection techniques used were interviews and questionnaires. The validity of student worksheets is carried out up to 3 stages, namely Analyze, Design, and Development. The results showed that the validity of the learner worksheet based on the results of validation from material experts on the material aspect obtained a percentage of 89.7% including in the